Bersinergi Dalam Penentuan Eksternalitas Objek Wisata Desa Sumbergondo Banyuwangi - Dofir Surya Saputra; Mohammad Kholil; Yeti Rahayu; Dyna Tauhidah; Reza Fatmatus Salwa (BADAN PENERBIT STIEPARI PRESS, 2023)
Tourism in a regional area has an influence on the economy of the regional community which can cause externalities, an externality is an activity of one party that affects another party without any accountability from the first party, this understanding is a negative externality which describes an impact that is not desired by other parties. The purpose of this service is to know the externalities that occur and efforts to overcome the externalities that occur. This trial was conducted using the Participation Action Research method. The results of this service are the positive externalities that occur in the Sumbergondo village tourism object, namely an increase in community income, employment, increased quality of life for the community, reduced unemployment, increased village income, development of MSMEs. The negative externalities that occur are noise, damaged infrastructure, traffic jams and social inequality or disparities and the community's expectations for the negative externalities that occur, namely the distribution of development considering that there are natural resources that need to be utilized properly.